Pengembangan Usaha Hidroponik di Syifa Hidroponik Kecamatan Medan Denai - Octasella Ainani As'ad; Nurhadida Nasution; Mariana Eva Yanti; Supriadi Surbakti; Sukri Mulia; Yusra Yurizki (PT. Karya Inovatif Nusantara, 2024)
This community service activity aims to: (1) Provide broad understanding and knowledge about hydroponic planting technology; (2) Providing development of innovation opportunities for derivative products in hydroponic water spinach plants and other plants; (3) Providing insight and motivating MSME players and prospective MSME players to increase their production and income; (4) Creating prosperous MSMEs as the main sector to influence income values ​​in Medan City; (5) Creating MSMEs that are very influential in improving the welfare of the people in Medan City. The activity method is carried out through discussion and mentoring. The objects of this community service are 10 Hydroponic MSMEs. Based on the results of community service activities, it can be concluded that there are 4 strategies in developing hydroponic businesses, namely: Product Strategy (product) to improve product quality. The pricing strategy used by hydroponic entrepreneurs is to adjust prices to competitors and adjust according to the quality of their products. The place strategy is that hydroponic entrepreneurs use their own private land. This aims to make it easier for entrepreneurs to monitor the processing and growth process of vegetable plants and make it easier for consumers to carry out transactions. The promotion strategy is to have good relations with customers, collaborate with one of the shops and carry out promotions via social media